Allelopathy Test of Reeds (Imperata cylindrica) on Germination and Early Growth of Green Beans (Vigna radiata L): Uji Alelopati Alang-Alang (Imperata cylindrica) Pada Perkecambahan Dan Pertumbuhan Awal Kacang Hijau (Vigna radiata L) - Susilo, Bagas Sadam Mas; Indarwati, Indarwati; Susilo, Achmadi (Journal of Applied Plant Technology, 2024)
The weed known as "Alang-alang" (Imperata cylindrica) has narrow leaves and grows in upright clusters. The allelopathic chemicals contained in alang-alang have a negative effect on the germination and early growth of other plants. The purpose of this research is to determine whether alang-alang has a negative effect on the germination and early growth of mung bean plants. The Laboratory of the Faculty of Agriculture, Wijaya Kusuma University, Surabaya, was the location of this research, conducted from November 2023 to January 2024. The research was conducted in the laboratory to test seed viability and in the field (planting in polybags) to test the early growth of plants. The research used a Completely Randomized Design (CRD), with 4 treatments: A0, which is water control; A1: 50 grams/ liter of water ; A2: 100 grams /liter of water; A3: 150 grams /liter of water; with 6 replications. The results of this research show for laboratory research: (1) the addition of extra alang-alang allelopathy did not significantly affect the germination of mung beans but the germinated seeds were able to grow abnormally. The allelopathy treatment test from 50 to 150 g/L of water; the tested mung bean seeds still grew 100%, but 91% to 100% of the seedlings became abnormal. (2) The addition of extra alang-alang allelopathy in polybag research did not affect the growth of the number of seedlings, seedling height, number of leaves, but negatively affected stem diameter and plant wet weight.